An observational study of Typhoon Khanun (2017) during intensification over the South China Sea. (23rd November 2022) - Liu, Fu; Hon, Kai‐kwong; Zhang, Han; Ming, Jie
Abstract: An observational study on the characteristics of Typhoon Khanun (2017) was conducted using lightning observations, global positioning system dropsonde observations, satellite‐derived precipitation, infrared‐derived brightness temperature and reanalysis data during its intensification stage. The characteristics of the tropical cyclone (TC) eye or eyewall have been captured for Typhoon Khanun over the South China Sea for the first time using dropsonde observations in recent years. The relationship between lightning evolution and the intensification of TCs was examined, and it was found that the lightning strokes within a 500‐km radius decreased as the typhoon intensified, while the lightning within 100 km (inner‐core) was inactive until 11 h prior to the peak intensity of Khanun. The burst of inner‐core lightning overlapped with the final intensification period of Khanun, indicating that the end of the inner‐core lightning burst may be an indicator of the termination of the intensification stage of TCs. Furthermore, a cyclonic rotation of inner‐core lightning was possibly related to the intensification of TCs influenced by the diabatic heating inside the radius of maximum wind. The dropsonde observations revealed that high water content within the mixed‐phase layer favoured the lightning activity and the convection system. Overall, this study promotes an in‐depth understanding of the linkage between lightning and the intensification of TCs along with the convection system. Abstract : Spatial distribution of hourly lightning strikes in the inner‐core (within 100 km) from October 14, 20:00 UTC to October 15, 09:00 UTC with respect to 850–200 hPa vertical wind shear. Each grey ring represents 25 km in an outward direction for 100 km. The black ring represents the location of RMW obtained from JTWC best track data. The black vector in each panel represents the direction of vertical wind shear, which is rotated around the TC center and points north. The colored dots indicate the hourly lightning at different times.